Cookies Daun Kelor sebagai Produk OVOP: Upaya Pemberdayaan Ekonomi dan Gizi di Desa Tegal - Suci Nuralita; Endang Silaningsih; Tini Kartini; Sri Harini; Yulianingsih Yulianingsih; Erni Yuningsih; Riny Kusumawati (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Village economic empowerment through the One Village One Product (OVOP) concept can improve community welfare. Tegal Village, Bogor Regency, has the potential of Moringa leaves (Moringa oleifera), which are rich in nutrients and can be used as healthy food to help prevent stunting. This study aims to develop Moringa leaf-based cookies as an innovative OVOP product to improve the village economy and address stunting. The method used is Participatory Action Research (PAR), involving PKK women in cookie-making training, and an experimental approach to find the best formulation. The results show that Moringa leaf cookies have high nutritional value, a crunchy texture, a pleasant taste, and good market potential. This activity also enhances women's skills in processing local ingredients into high-value products. With this innovation, the community gains both nutritional benefits and new business opportunities through MSME development. This product is expected to become a sustainable village flagship and support efforts to reduce stunting rates. The results demonstrate local resource-based innovation as an effective solution for improving community welfare and health.